Kikuchi–Fujimoto Disease Presenting as Brachial Plexus Neuritis: A Case Report - Rakesh Gupta; Akshat Kayal; Vishwesh Rajawat (Indian Journal of Neurosurgery)
Abstract Kikuchi–Fujimoto disease is a rare, idiopathic, self-limiting necrotizing lymphadenitis of unknown etiology. It usually affects young Asian women. Clinically, it closely resembles with tuberculosis or lymphomas. This pathology has occasionally been associated with various cardiac, renal, pulmonary, and other systemic complications. The association of the disease in context to other neurological pathologies is even more sporadic. We report a case of Kikuchi–Fujimoto disease in a 56-year-old woman associated with the rare presentation as brachial plexus neuritis. The diagnosis was established histopathologically upon surgical resection of lesion. We discuss the peculiar features of presentation, pathological elements, surgical management, and postoperative outcome with special emphasis on complications of this clinical entity.